2010
DOI: 10.1038/ajh.2009.270
|View full text |Cite
|
Sign up to set email alerts
|

Additive Beneficial Effects of Lactotripeptides Intake With Regular Exercise on Endothelium-Dependent Dilatation in Postmenopausal Women

Abstract: We concluded that LTP ingestion combined with regular aerobic exercise improves endothelium-dependent dilatation to a greater extent than monotherapy with either intervention alone in postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 21 publications
(24 reference statements)
3
63
0
Order By: Relevance
“…A positive effect was observed in the US, 7 Japanese 8 and southern European subjects, 9 but not in northern Europeans. 10 In Japanese subjects only, investigations confirmed an effect of LTP on flow-mediated dilation, 11 artery compliance, 12 and central BP. 13 Because the antihypertensive effect of LTPs seems to be strongly related to the ethnicity of patients, 6 it would be beneficial to increase our understanding of the effect of these nutraceuticals on different cardiovascular parameters in European subjects.…”
Section: Introductionmentioning
confidence: 99%
“…A positive effect was observed in the US, 7 Japanese 8 and southern European subjects, 9 but not in northern Europeans. 10 In Japanese subjects only, investigations confirmed an effect of LTP on flow-mediated dilation, 11 artery compliance, 12 and central BP. 13 Because the antihypertensive effect of LTPs seems to be strongly related to the ethnicity of patients, 6 it would be beneficial to increase our understanding of the effect of these nutraceuticals on different cardiovascular parameters in European subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Cicero et al (55) also reported a significant improvement in pulse wave velocity (20·66 (SD 0·81) m/s; P¼0·001), stroke volume, stroke volume index, acceleration index and velocity index after 6 weeks of treatment with LTP (3 mg/d) in fifty subjects, though these changes were relative to baseline. Yoshizawa et al (48,49) investigated the combined effect of exercise and LTP consumption on endothelium-dependent dilatation and carotid arterial compliance in postmenopausal women. They found significant improvements in both flow-mediated dilatation and arterial compliance in response to LTP, LTP þ exercise, and exercise þ placebo groups, but not in the placebo group, and concluded that whilst LTP had a beneficial effect on vascular function, the addition of exercise produced a synergistic effect.…”
Section: á a Fekete Et Almentioning
confidence: 99%
“…The Panel notes that 15 RCTs Cicero et al, 2010;De Leeuw et al, 2009;Engberink et al, 2008;Itakura et al, 2001;Mizushima et al, 2004;Seppo et al, 2003;Tuomilehto et al, 2004;Turpeinen et al, 2009;Usinger et al, 2010a;Van der Zander et al, 2008a;Van der Zander et al, 2008b;Van Mierlo et al, 2009 two studies;Yoshizawa et al, 2010), of which seven were designed to detect small (3-9 mm Hg) differences in SBP De Leeuw et al, 2009;Usinger et al, 2010a;Van der Zander et al, 2008a;Van der Zander et al, 2008b;Van Mierlo et al, 2009 two studies), did not observe an effect of IPP and VPP on SBP or DBP.…”
Section: Scientific Substantiation Of the Claimed Effect (Id 661 183mentioning
confidence: 99%
“…In the framework of further assessment, two additional meta-analyses (Aubin, 2011, unpublished;Cicero et al, 2011) and six RCTs (Cicero et al, 2010;Ishida et al, 2007;Nakamura et al, 2011;Turpeinen et al, 2009;Usinger et al, 2010a;Yoshizawa et al, 2010) were provided as pertinent to the claim.…”
Section: Scientific Substantiation Of the Claimed Effect (Id 661 183mentioning
confidence: 99%
See 1 more Smart Citation